2015
DOI: 10.4049/jimmunol.1401663
|View full text |Cite
|
Sign up to set email alerts
|

The MAPK-Activated Kinase MK2 Attenuates Dendritic Cell–Mediated Th1 Differentiation and Autoimmune Encephalomyelitis

Abstract: Dendritic cell (DC)–mediated inflammation induced via TLRs is promoted by MAPK-activated protein kinase (MK)-2, a substrate of p38 MAPK. In this study we show an opposing role of MK2, by which it consolidates immune regulatory functions in DCs through modulation of p38, ERK1/2-MAPK, and STAT3 signaling. During primary TLR/p38 signaling, MK2 mediates the inhibition of p38 activation and positively cross-regulates ERK1/2 activity, leading to a reduction of IL-12 and IL-1α/β secretion. Consequently, MK2 impairs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
5
17
0
Order By: Relevance
“…Our in vitro experiments however, in both murine and human systems, demonstrated a clear role of MK2 in broad macrophage biology, including polarization into M2 macrophages and macrophage production of proangiogenic factors, consistent with the proposed mechanism for the observed mouse phenotypes. A functional role for MK2 in other myeloid cell types, including neutrophils and dendritic cells (39)(40)(41), could also contribute to the observed phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Our in vitro experiments however, in both murine and human systems, demonstrated a clear role of MK2 in broad macrophage biology, including polarization into M2 macrophages and macrophage production of proangiogenic factors, consistent with the proposed mechanism for the observed mouse phenotypes. A functional role for MK2 in other myeloid cell types, including neutrophils and dendritic cells (39)(40)(41), could also contribute to the observed phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, sequestration of p38 cannot be the only explanation for this, ando ur data contradict previous literature reports. [2] More recent scientific reports [25][26][27][28][29][30][31] demonstrate that IL-10 is directly regulated by MK2 in addition to MSK1. As such, our data invalidate MK2 as at arget for selective inhibition of inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Roberts et al found that PI3k activated by CR3 ligation led to the upregulation of MKP-1, which can inhibit p38 MAPK and thereby suppress the inflammatory response [173]. Soukup et al described that a similar effect was mediated by MK2, which could inhibit TLR-mediated inflammatory responses triggered by LPS [154]. None of these factors appear to be significantly affected in our transcriptomic studies, but their involvement cannot be excluded as upregulation of these factors is transient.…”
Section: Tlr-cr Crosstalkmentioning
confidence: 58%
“…None of these factors appear to be significantly affected in our transcriptomic studies, but their involvement cannot be excluded as upregulation of these factors is transient. Soukup et al measured MK2 expression at 6h, 12h, 24h and 48h, but could only detect upregulation at 24h [154]. As previously mentioned, a setting where p38 MAPK and NFkβ signaling is stronger leads to an inflammatory response, whereas if PI3K/AKT and ERK dominate, inflammation is dampened [146].…”
Section: Tlr-cr Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation